Understanding Agenda Setting in State Educational Policy: An Application of Kingdon’s Multiple Streams Model to the Formation of State Reading Policy - Young, Tamara Viola; Shepley, Thomas V.; Song, Mengli (Education Policy Analysis Archives, 2010)
Drawing on interview data from reading policy actors in California, Michigan, and Texas, this study applied Kingdon's (1984, 1995) multiple streams model to explain how the issue of reading became prominent on the agenda of state governments during the latter half of the 1990s. A combination of factors influenced the status of a state's reading policy agenda, including feedback from parents, teachers, and business groups; student achievement data; political pressure from the state administration; regional and national interest; a pervasive belief that reading is a building block for student success; and a widespread perception that the decline in reading achievement was symbolic of the failure of public schools. In addition, governors promoted reading to high agenda prominence by influencing which issues were placed on the decision agenda (agenda setting) and which alternatives were given serious attention (alternative specification). Finally, the findings suggest that the applicability of Kingdon's national-level model to the state level may depend on both the issue being examined and the participation of the state executive branch.